Patterns of practice of adaptive re-planning for anatomic variances during cone-beam CT guided radiotherapy. (December 2019) - Stankiewicz, Michal; Li, Winnie; Rosewall, Tara; Tadic, Tony; Dickie, Colleen; Velec, Michael
Highlights: RTTs report substantial anatomic variances during cone-beam CT guided radiotherapy. These variances led to unscheduled adaptive re-planning in 21% of cases. Suspected tumor progression was a frequent cause of re-planning. Understanding clinical scenarios for re-planning will enable more formal adaptive strategies to be developed. Abstract: Purpose: Substantial, unanticipated anatomic variances during cone-beam CT (CBCT)-guided radiotherapy can potentially impact treatment accuracy and clinical outcomes. This study assessed patterns of practice of CBCT variances reported by RTTs and subsequent interventions for multiple-disease sites. Methods: A chart review was conducted at a large cancer centre for patients treated with daily online CBCT-guided radiotherapy. Patients selected for review were identified via RTT-reported variances that then triggered offline multi-disciplinary assessment. Cases were categorized by the type of anatomic variance observed on CBCT and any further interventions recorded such as un-scheduled adaptive re-planning. Results: Over a 1-year period, 287 variances from 261 patients were identified (6.2% of the 4207 patients treated with daily CBCT-guided radiotherapy), most often occurring within the first 5 fractions of the treatment course. Of these variances, 21% (59/287) were re-planned and 3.5% (10/287) discontinued treatment altogether. Lung was the most frequent disease-site (27% of 287 variances) reported with IGRT-related variances although head and neck and sarcoma were most frequently re-planned (19% of 59 re-plans for each site). Technical or clinical rationales for re-planning were not routinely documented in patient medical records. All disease-sites had numerous categories of variances. Three of the four most frequent categories were for tumor-related changes on CBCT, and the re-planning rate was highest for tumor progression at 25%. Normal tissue variances were the second most frequency category, and re-planned in 14% of those cases. Conclusion: RTTs identified a wide range of anatomic variances during CBCT-guided radiotherapy. In a minority of cases, these substantially altered the care plan including ad hoc adaptive re-planning or treatment discontinuation. Improved understanding of the clinical decisions in these cases would aid in developing more routine, systematic adaptive strategies.